Biofeedback en suelo pélvico. - Trujillo Cando, Aracely Estefanía (2024)
The pelvic floor is a vital structure of the human body that supports the pelvic organs in their respective positions so that they can correctly fulfill their function. Dysfunction of these muscles increases the risk of suffering pelvic floor disorders such as urinary and fecal incontinence. The objective of the present investigation was to determine the effects of the biofeedback technique by collecting scientific articles on patients with pelvic floor dysfunction. The research was meticulously conducted through a bibliographic design study, documentary type, and inductive method on the topic 'Biofeedback in the pelvic floor'. This involved collecting and analyzing scientific articles published between 2013-2023 from reputable databases such as Pubmed, ResearchGate, ScienceDirect, Scielo, and Cochrane Library. A total of 35 articles were then carefully validated according to the PEDro scale. The results of our study revealed that biofeedback is a highly effective intervention that strengthens and relaxes the pelvic musculature. This technique significantly contributes to the improvement of pelvic floor dysfunctions, such as urinary and fecal incontinence. Importantly, it also has a profound positive impact on the emotional and social well-being of patients, thereby enhancing their overall quality of life.